The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3390/challe5010100
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges Associated with the Development of Forest-Based Bioenergy Projects in India: Results from an Expert Survey

Abstract: Development of energy systems, based on forest biomass, is a challenging issue in India. The study investigated perceptions of fifty-five Indian Forest Service (IFS) officers in relation to the potential benefits and challenges associated with the development of forest-based bioenergy (FBE) projects in India when they participated in two training programs in Finland during 2010. They generally agreed that development of FBE projects could have beneficial impacts on job creation, income generation, rural develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In an Indian context, there have been a few techno-economic studies regarding the opportunities and challenges concerning bioenergy development; however, none have focused on FBPs, perhaps due to the reason that conversion technologies for second generation biofuels have not been developed in the country [23]. Most recently, Halder et al [9] conducted a study among a group of professionals working in the Indian Forest Service (IFS) to explore their perceptions of developing FBPs in India. Their study found that while the IFS professionals perceived that such projects could create jobs and income, they were also concerned over the lack of public awareness and political support, as well as the lack of suitable technologies for such projects in India.…”
Section: Experts' Perceptions Of Energy Production From Forest Biomassmentioning
confidence: 98%
See 2 more Smart Citations
“…In an Indian context, there have been a few techno-economic studies regarding the opportunities and challenges concerning bioenergy development; however, none have focused on FBPs, perhaps due to the reason that conversion technologies for second generation biofuels have not been developed in the country [23]. Most recently, Halder et al [9] conducted a study among a group of professionals working in the Indian Forest Service (IFS) to explore their perceptions of developing FBPs in India. Their study found that while the IFS professionals perceived that such projects could create jobs and income, they were also concerned over the lack of public awareness and political support, as well as the lack of suitable technologies for such projects in India.…”
Section: Experts' Perceptions Of Energy Production From Forest Biomassmentioning
confidence: 98%
“…Results from the India-specific study have been published in Halder et al [9], and therefore, this study will only present the results of the comparative analysis between the two countries. Data were collected from a group of Indian SFPs when they participated in a forestry training program in Finland in 2010.…”
Section: Survey Instrument Design and Data Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…Improved energy access and quality of life: Solar-powered agriculture can improve energy access and quality of life for rural communities, particularly in developing countries where access to electricity is limited or unreliable [113]. By providing a sustainable and affordable source of energy for farming and household uses, solarpowered systems can reduce the time and labor required for tasks such as water collection, cooking, and lighting, freeing up time for education, income-generating activities, and leisure [114].…”
Section: Social and Health Benefitsmentioning
confidence: 99%
“…In addition, various challenges associated with the development of large-scale bioenergy projects are recognized as: lack of available land for energy crop plantations; lack of information on the impacts of bioenergy production on food security; and lack of institutional, financial, and initiatives in promotion of bioenergy marketing [11]. A recent study revealed that lack of public acceptance, political support, available technology, and infrastructure are the major hindrances in the development of forest-based bioenergy projects in India [12]. However, the above bottlenecks are very common in the promotion of bioenergy, not only in India but also in other developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%